2017
DOI: 10.1109/tr.2016.2628759
|View full text |Cite
|
Sign up to set email alerts
|

A Similarity Metric for the Inputs of OO Programs and Its Application in Adaptive Random Testing

Abstract: Abstract-Random testing (RT) has been identified as one of the most popular testing techniques, due to its simplicity and ease of automation. Adaptive random testing (ART) has been proposed as an enhancement to RT, improving its fault-detection effectiveness by evenly spreading random test inputs across the input domain. To achieve the even spreading, ART makes use of distance measurements between consecutive inputs. However, due to the nature of object-oriented software (OOS), its distance measurement can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…Some earlier research studies have shown that the probability of achieving higher failure-detection is by evenly spreading test cases across the input domain [3][4][5][6]. RT, although has lower effectiveness, has almost a linear efficiency as its algorithm selects test cases randomly from the input domain without considering their even spread.…”
Section: Introductionmentioning
confidence: 99%
“…Some earlier research studies have shown that the probability of achieving higher failure-detection is by evenly spreading test cases across the input domain [3][4][5][6]. RT, although has lower effectiveness, has almost a linear efficiency as its algorithm selects test cases randomly from the input domain without considering their even spread.…”
Section: Introductionmentioning
confidence: 99%
“…• Some studies found ART to be more cost-effective than RT (e.g., [114], [150], [166]), with some observing ART to require less time than RT to identify the first failure (e.g., [40], [144]).…”
Section: Summary Of Main Results For Application Domainsmentioning
confidence: 99%
“…Although many approaches have been proposed for ART, there are very few tools [40], [73], [114], [144], [150], some of which are: AutoTest, which supports ART for objectoriented (ARTOO) programs written in Eiffel [40]; ART-Gen, which supports divergence-oriented ART for Java programs [114]; Practical Extensions of Random Testing (PERT), which supports testing for various input types [150]; and OMISS-ART, which supports FSCS for C++ and C# programs. However, these tools are not publicly available.…”
Section: Challenge 6: Art Toolsmentioning
confidence: 99%
“…For instance, a linear-time ARTsum algorithm was recommended by Barus et al [32] using the concepts of categories and choices in category-partition testing. Ciupa et al [8] and Chen et al [9] introduced the ARTOO and the OMISS metrics for modeling the distances between objects and between method innovation sequences. We have not compared RRT-LAZ with these algorithms experimentally because they cater for non-numerical inputs.…”
Section: Further Discussion On Related Workmentioning
confidence: 99%